Modifiable and Nonmodifiable Factors Associated With Perioperative Failure of Extraglottic Airway Devices. (June 2018) - Vannucci, Andrea; Rossi, Isabella T.; Prifti, Kevin; Kallogjeri, Dorina; Rangrass, Govind; DeCresce, David; Brenner, Daniel; Lakshman, Neel; Helsten, Daniel L.; Cavallone, Laura F.
Abstract : BACKGROUND: Extraglottic airway device (EGA) failure can be associated with severe complications and adverse patient outcomes. Prior research has identified patient- and procedure-related predictors of EGA failure. In this retrospective study, we assessed the incidence of perioperative EGA failure at our institution and identified modifiable factors associated with this complication that may be the target of preventative or mitigating interventions. METHODS: We performed a 5-year retrospective analysis of adult general anesthesia cases managed with EGAs in a single academic center. Univariable and multivariable logistic regressions were used to identify clinically modifiable and nonmodifiable factors significantly associated with 3 different types of perioperative EGA failure: (1) "EGA placement failure, " (2) "EGA failure before procedure start, " and (3) "EGA failure after procedure start." RESULTS: A total of 19, 693 cases involving an EGA were included in the analysis dataset. EGA failure occurred in 383 (1.9%) of the cases. EGA placement failure occurred in 222 (1.13%) of the cases. EGA failure before procedure start occurred in 76 (0.39%) of the cases. EGA failure after procedure start occurred in 85 (0.43%) of the cases. Factors significantly associated with each type of failure and controllable by the anesthesia team were as follows: (1) EGA placement failure: use of desflurane (odds ratio [OR], 1.67; 95% confidence interval [CI], 1.23–2.25) and EGA size 4 or 5 vs 2 or 3 (OR, 0.07; 95% CI, 0.05–0.10); (2) EGA failure before procedure start: use of desflurane (OR, 2.05; 95% CI, 1.23–3.40) and 3 or more placement attempts (OR, 4.69; 95% CI, 2.57–8.56); and (3) EGA failure after procedure start: 3 or more placement attempts (OR, 2.06; 95% CI, 1.02–4.16) and increasing anesthesia time (OR, 1.35; 95% CI, 1.17–1.55). CONCLUSIONS: The overall incidence of EGA failure was 1.9%, and EGA placement failure was the most common type of failure. We also found that use of desflurane and use of smaller EGA sizes in adult patients were factors under the direct control of anesthesia clinicians associated with EGA failure. An increasing number of attempts at EGA placement was associated with later device failures. Our findings also confirm the association of EGA failure with previously identified patient- and procedure-related factors such as increased body mass index, male sex, and position other than supine.